2006
DOI: 10.1105/tpc.105.037671
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Arabidopsis Lacking Starch Branching Enzyme II Substitute Plastidial Starch Synthesis by Cytoplasmic Maltose Accumulation

Abstract: Three genes, BE1, BE2, and BE3, which potentially encode isoforms of starch branching enzymes, have been found in the genome of Arabidopsis thaliana. Although no impact on starch structure was observed in null be1 mutants, modifications in amylopectin structure analogous to those of other branching enzyme II mutants were detected in be2 and be3. No impact on starch content was found in any of the single mutant lines. Moreover, three double mutant combinations were produced (be1 be2, be1 be3, and be2 be3), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 56 publications
10
130
1
2
Order By: Relevance
“…There are three SBE genes in Arabidopsis. SBE1 has no apparent function in starch metabolism in Arabidopsis leaves, but SBE2 and SBE3 are required for starch synthesis (Dumez et al, 2006). SBE3 gene expression changes within the diurnal cycle, whereas SBE1 and SBE2 expression undergoes minor fluctuations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three SBE genes in Arabidopsis. SBE1 has no apparent function in starch metabolism in Arabidopsis leaves, but SBE2 and SBE3 are required for starch synthesis (Dumez et al, 2006). SBE3 gene expression changes within the diurnal cycle, whereas SBE1 and SBE2 expression undergoes minor fluctuations .…”
Section: Discussionmentioning
confidence: 99%
“…It is synthesized mainly during photosynthesis in the light period buffering CO 2 fixation or in storage organs like tubers, bulbs, or seeds (Dennis and Blakeley, 2000). In recent years, numerous studies have been performed to increase knowledge of starch metabolism, including in the model plant Arabidopsis (Arabidopsis thaliana; Zeeman et al, 2002Zeeman et al, , 2004Siedlecka et al, 2003;Smith et al, 2004;Delvallé et al, 2005;Lloyd et al, 2005;Dumez et al, 2006). In most of these studies, plant leaf material of the wild type and mutant lines was used to investigate starch metabolism under different light regimes or altered sugar concentrations.…”
mentioning
confidence: 99%
“…Arabidopsis (Arabidopsis thaliana L.) has two SBEII-class enzymes termed SBE 2.1 and SBE 2.2 (47), plus a third unrelated form which is not expressed and has no known function. Deletion of either active isoform has minimal effect on starch synthesis, whereas simultaneous loss of both SBEII forms from Arabidopsis results in a failure to synthesize starch and accumulation of maltose in the cytosol (48). Some enzymes of starch biosynthesis are found strongly associated with starch granules, including SBEII isoforms from a range of species (49)(50)(51)(52).…”
Section: Tablementioning
confidence: 99%
“…BE1 belongs to a novel SBEIII class (Han et al, 2007), for which a putative homolog has recently been identified in the maize genome (Yan et al, 2009). BE1 is apparently not required for transitory starch synthesis in Arabidopsis (Dumez et al, 2006). In pea leaves, approximately 90% of the SBE activity is accounted for by a single class II SBE, SBE A, and the remaining 10% by a class I enzyme, SBE B (Tomlinson et al, 1997).…”
Section: Transitory Starch Synthesis And/or Degradation Differ Betweementioning
confidence: 99%
“…BE1, BE2, and BE3) are active in the leaf (Fisher et al, 1996a;Khoshnoodi et al, 1998;Dumez et al, 2006). BE2 and BE3, class IIa SBEs with similarity to maize SBEIIa, contribute significantly to the synthesis of transitory starch.…”
Section: Transitory Starch Synthesis And/or Degradation Differ Betweementioning
confidence: 99%